A study on the job satisfaction of professional librarians doing support staff duties in libraries within the University of the Philippines - Santos, Paul L.
A total of 41 respondents were surveyed from 22 libraries within the university. The questionnaire was based after the one prepared by Gonda and was modified to suit the objectives of the study. Data regarding professional and support staff duties were all retrieved from the University's REPS PES form and was used as reference material for the job satisfaction part of the survey questionnaire.